1997
DOI: 10.1113/jphysiol.1997.sp021953
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular alkalinization mobilizes calcium from agonist‐sensitive pools in rat lacrimal acinar cells.

Abstract: 1. We have investigated interactions between intracellular pH (pHJ) and the intracellular free calcium concentration ([Ca2+]i) in collagenase-isolated rat lacrimal acinar cells. The fluorescent dyes fura-2 and 2',7'-bis(carboxyethyl)-5-carboxyfluorescein (BCECF) were used to measure [Ca2+] Ca2+ from the intracellular agonist-sensitive Ca2+ pool. However, releasing stored Ca2+ via alkalinization does not appear to trigger significant Ca2+ entry, perhaps because intracellular alkalinization inhibits either the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 43 publications
6
35
0
Order By: Relevance
“…] i changes in response to pH e changes Based on previous studies in trout hepatocytes (Walsh, 1986;Krumschnabel et al, 2001b) e , which is consistent with observations in smooth muscle cells (Siskind et al, 1989), rat pheochromocytoma cells (Dickens et al, 1989), bovine lactotrophs (Zorec et al, 1993), rat lacrimal (Yodozawa et al, 1997) and pancreatic acinar cells (Speake and Elliott, 1998) but not with those in rat lymphocytes (Grinstein and Goetz, 1985) ] i (Grinstein and Goetz, 1985 e inhibited this mechanism, resulting in a slower pHi recovery (Fig.·6A). Looking at the peak of pHi increase in response to NH 4 Cl exposure, the difference between the control treatment, on the one hand, and the absence of Ca e was recorded in rat pheochromocytoma cells (Dickens et al, 1989) and vascular smooth muscle (Dickens et al, 1989;Batlle et al, 1993) while no effect on [Ca 2+ ] i has been reported in toxoplasma gondii tachyzoites (Moreno and Zhong, 1996) and rat pancreatic acinar cells (Speake and Elliott, 1998).…”
Section: +supporting
confidence: 74%
See 1 more Smart Citation
“…] i changes in response to pH e changes Based on previous studies in trout hepatocytes (Walsh, 1986;Krumschnabel et al, 2001b) e , which is consistent with observations in smooth muscle cells (Siskind et al, 1989), rat pheochromocytoma cells (Dickens et al, 1989), bovine lactotrophs (Zorec et al, 1993), rat lacrimal (Yodozawa et al, 1997) and pancreatic acinar cells (Speake and Elliott, 1998) but not with those in rat lymphocytes (Grinstein and Goetz, 1985) ] i (Grinstein and Goetz, 1985 e inhibited this mechanism, resulting in a slower pHi recovery (Fig.·6A). Looking at the peak of pHi increase in response to NH 4 Cl exposure, the difference between the control treatment, on the one hand, and the absence of Ca e was recorded in rat pheochromocytoma cells (Dickens et al, 1989) and vascular smooth muscle (Dickens et al, 1989;Batlle et al, 1993) while no effect on [Ca 2+ ] i has been reported in toxoplasma gondii tachyzoites (Moreno and Zhong, 1996) and rat pancreatic acinar cells (Speake and Elliott, 1998).…”
Section: +supporting
confidence: 74%
“…Alteration in pH e below and above normal values induced a slow, continuous increase in [Ca cultured smooth muscle cells (Siskind et al, 1989), lacrimal acinar cells (Yodozawa et al, 1997) and endothelial cells (Danthuluri et al, 1990).…”
Section: +mentioning
confidence: 99%
“…Increases of pH i generally stimulate cartilage synthesis whereas decreases inhibit it [23]. Furthermore, perturbation of pH i causes alterations in the intracellular concentrations of a variety of cations in other cell types [4,27]. Such changes can be a consequence of the operation of transporters regulating pH i , or a direct effect of altered numbers of intracellular acid equivalents.…”
Section: Introductionmentioning
confidence: 97%
“…The results of such studies have depended on the cell type and the manner in which acidification/alkalinization of the cell was elicited. Alkalinization in most cases appeared to enhance CCE, while acidification reduced entry [Danthuluri et al, 1990;Laskay et al, 2005;Li et al, 2000;Malayev et al, 1995;Marumo and Wakabayashi, 2005;Muallem et al, 1989;Sepulveda et al, 2000;Wojnowski et al, 1994;Yodozawa et al, 1997]. In many studies, alkalinization was reported to cause release of intracellular calcium [Minelli et al, 2000;Muallem et al, 1989;Wojnowski et al, 1994;Yagodin et al, 1999;Yodozawa et al, 1997].…”
Section: Discussionmentioning
confidence: 95%
“…Since CCE is markedly reduced upon acidification of cells (see below), studies at varying pHs were then conducted with loperamide after ATP-stimulated release of intracellular calcium. The effects of acidification/alkalinization of external media on calcium release from internal stores and on CCE have been extensively studied in various cell lines [Danthuluri et al, 1990;Laskay et al, 2005;Li et al, 2000;Malayev et al, 1995;Marumo and Wakabayashi, 2005;Minelli et al, 2000;Muallem et al, 1989;Sepulveda et al, 2000;Wojnowski et al, 1994;Yagodin et al, 1999;Yodozawa et al, 1997]. In some cases, high extracellular concentrations of NH 4 Cl have been used to elicit the alkalinization of cells.…”
Section: Discussionmentioning
confidence: 99%